A língua portuguesa e os média nas vivências de imigrantes nepaleses em Portugal - Branco Inês Miradouro (Revista Comunicando, 2012)
The research focuses on Nepalese immigrant community living in Portugal and on how immigrants use different media – from host country, homeland and global – to connect and preserve the original culture, on the one hand, and in the process of adaptation and integration into the host culture, on the other. The study was based on in-depth interviews, semi-structured, focusing on the journey of life, the uses of media and the use of Portuguese language. The findings of this exploratory study show the importance that media have at different periods of immigrant’s lives, depending on the state of integration into host society. In forming a new identity where values and customs of different cultures mix together, in adjusting to a new place of living, and in maintaining connections to family and cultural past, immigrants find on media tools that help them overcome some of the key barriers inherent to the migration process, in particular, on learning the host language.